Effects of age and seasonal temperatures on cortisol levels and GHR, IGF-I, and IGF-II expressions in rainbow trout (Oncorhynchus mykiss) - Tekeli, H; Bildik, A (Journal of the Hellenic Veterinary Medical Society, 2023)
The growth hormone (GH)/insulin-like growth factor (IGF) endocrine axis regulates the cellular growth and organ development in related to changing environmental conditions and age. The aim of this study is to determine growth factor genes, which are biological markers of growth in muscle and liver of rainbow trout (Oncorhynchus mykiss) in different seasonal temperatures and age ranges and the reveal of the relationship between serum cortisol (COR) levels from stress parameters. No difference was found in serum COR levels between the groups with respect to temperature and age. Serum GH levels were found to be higher in the summer juvenile trout compared to the winter juvenile and adult trouts. There was no difference in liver growth hormone receptor (GHR) mRNA levels of juvenile and adult trouts in winter while insulin-like growth factor-I (IGF-I) and insulin-like growth factor-II (IGF-II) mRNA levels in liver and muscle tissues were found to be higher in juvenile trout compared to adults. Among trout of different ages, GHR, IGF-I and IGF-II mRNA levels in liver in summer were higher for juvenile trout compared to adults. Muscle IGF-I mRNA levels in summer were higher in adult trout compared to juveniles. IGF-II mRNA levels in liver and muscle tissues of juvenile trout showed an increase in winter compared to in summer. While the GHR and IGF-II mRNA levels in the liver tissue of adult trout were observed to higher in winter compared to summer, IGF-I mRNA levels were found to be higher in summer. GHR, IGF-I and IGF-II mRNA levels in muscle tissue of adult trout were found to be higher in summer than in winter. This study indicated that juvenile and adult rainbow trout (Oncorhynchus mykiss) are adapted to both winter and summer temperature and that GHR, IGF-I and IGF-II genes are highly expressed.